Studi Empiris Tentang Pengaruh Kebutuhan Perusahaan Terhadap Pemeriksaan Akuntan Publik Di Jawa Tengah dan Implikasinya Terhadap Pengembangan Profesi Akuntan Publik - Nasir, Mohammad (JURNAL BISNIS STRATEGI, 1997)
This research is designed as an empirical research to investigate some factors influencing the manufacturing firms on the demand of public accountant services. These factors include  the company size, the amount of company's debt, and the number of stocks owned by management.The measurement of company size include its total assets,   equities,   sales, and the number  of emplofees. The measurement of total company's debt includes the percentage of company's  capital  structure  as  well as  total  debt  (current   and   longterm liabilities)  and  total equity (total stocks and retained earnings). The measurement of the number of stocks owned by  management include   the number of stock holders of the  company,   the number of stockholder  who actively  participated in  managing  the firm,   the percentage of the stocks  owned by  the  member of management and nonmember of management of the firm.For the sake of the research, 110 samples  of  manufacturing  firms  in Central Java were taken by using strati fied  random sampling.  The  samples were analyzed by regression method.  The research finding revealed that the com pany  size,  the company's debt,   and the number of stock owned by management significantly   influenced  the demand for external auditor services for the small, me diu ra,    and   large firms.  The bigger the company size and  the more  company's debt,  the greater  the possibility of   the firms required the audit services by public accountants.However,   the more stocks owned by management, the less the possibility of the finns  demand audited by public accountants.